Treatment strategies for erosive genital lichen planus: A systematic review of therapeutic modalities and emerging breakthroughs - Borna Safari‐Kish; Matin Bidares; Shirin Zaresharifi; Hesam Malekzadeh‐Shoushtari; Mahsa Aziz; Mahsa Salehi; Khatere Zahedi (Health Science Reports, 2024)
Abstract Background and Aims Erosive genital lichen planus (EGLP) is a severe form of lichen planus characterized by painful erosions in the genital area, leading to significant distress and complications. This review aims to provide a thorough examination of EGLP, focusing on its clinical manifestations, diagnostic challenges, and various treatment strategies, with an emphasis on patient‐centered care. Methods Adhering to PRISMA guidelines, we conducted a systematic review of 26 studies that explored dermatological treatments for EGLP. Our literature search was comprehensive, covering PubMed, Scopus, and Web of Science. Data were extracted systematically using established tools to ensure a robust analysis of the treatment modalities. Results EGLP presents with a range of symptoms, including severe pain, itching, and sexual dysfunction. Treatment options include topical corticosteroids, systemic medications, and surgical interventions. Despite the availability of various therapies, many cases are refractory to treatment, resulting in chronic symptoms and reduced quality of life. Emerging therapies show promise but are not yet established as standard practice. Conclusion Management of EGLP requires a tailored, multidimensional approach. While topical corticosteroids remain essential, the development of new therapies offers hope for improved outcomes. A patient‐centered approach is vital to address both the physical and psychosocial impacts of EGLP. Continued research is necessary to refine treatment protocols and enhance patient care.